2022
DOI: 10.1149/1945-7111/ac5d95
|View full text |Cite
|
Sign up to set email alerts
|

The Role of an In-Situ Grown Zn-Al Layered Double Hydroxide Conversion Coating in the Protective Properties of Epoxy Coating on Galvanized Steel

Abstract: A Zn-Al layered double hydroxide (LDH) conversion coating was investigated as a surface treatment for galvanized steel. Zn-Al LDH crystals were grown in-situ on the galvanized steel surface in room temperature at different periods. Grazing Incidence Xray Diffraction verified the formation of Zn-Al LDH flakes on the surface. Scanning Electron Microscopy showed that Zn-Al LDH flakes were evenly distributed as a continuous coating on the surface of galvanized steel. Roughness and surface free energy of the coatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…At present, many different preparation methods of LDH have been reported, such as in situ growth, [28,[40][41][42] co-deposition [34,43], and anion exchange methods. [44] LDH prepared by the in situ growth method has attracted a lot of attention from researchers due to its simple preparation process, strong coating adhesion, and remarkable corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…At present, many different preparation methods of LDH have been reported, such as in situ growth, [28,[40][41][42] co-deposition [34,43], and anion exchange methods. [44] LDH prepared by the in situ growth method has attracted a lot of attention from researchers due to its simple preparation process, strong coating adhesion, and remarkable corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…[17,18,[25][26][27] Therefore, it is speculated that ZnAl-LDH may be the main factor responsible for the improved corrosion resistance of Zn-Al coating. Furthermore, Sima et al [28] reported that the ZnAl-LDH can improve the corrosion resistance of galvanized steel. The dense corrosion product film containing LDH can effectively inhibit the diffusion of corrosive solution into the galvanized coating and prevent it from being eroded.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations